Allogeneic stem cell transplantation in patients with atypical chronic myeloid leukaemia: a retrospective study from the Chronic Malignancies Working Party of the European Society for Blood and Marrow Transplantation. (28th March 2017) - Onida, Francesco; de Wreede, Liesbeth C.; van Biezen, Anja; Eikema, Diderik‐Jan; Byrne, Jenny L.; Iori, Anna P.; Schots, Rik; Jungova, Alexandra; Schetelig, Johannes; Finke, Jürgen; Veelken, Hendrik; Johansson, Jan‐Erik; et al.
Summary: Atypical chronic myeloid leukaemia (aCML) is an aggressive malignancy for which allogeneic haematopoietic stem cell transplantation (allo‐HSCT) represents the only curative option. We describe transplant outcomes in 42 patients reported to the European Society for Blood and Marrow Transplantation (EBMT) registry who underwent allo‐HSCT for aCML between 1997 and 2006. Median age was 46 years. Median time from diagnosis to transplant was 7 months. Disease status was first chronic phase in 69%. Donors were human leucocyte antigen (HLA)‐identical siblings in 64% and matched unrelated (MUD) in 36%. A reduced intensity conditioning was employed in 24% of patients. T‐cell depletion was applied in 87% and 26% of transplants from MUD and HLA‐identical siblings, respectively. According to the EBMT risk‐score, 45% of patients were 'low‐risk', 31% 'intermediate‐risk' and 24% 'high‐risk'. Following allo‐HSCT, 87% of patients achieved complete remission. At 5 years, relapse‐free survival was 36% and non‐relapse mortality (NRM) was 24%, while relapse occurred in 40%. Patient age and the EBMT score had an impact on overall survival. Relapse‐free survival was higher in MUD than in HLA‐identical sibling HSCT, with no difference in NRM. In conclusion, this study confirmed that allo‐HSCT represents a valid strategy to achieve cure in a reasonable proportion of patients with aCML, with young patients with low EBMT risk score being the best candidates.